Edukasi Diabetes terhadap Penurunan Glukosa Darah pada Penderita Diabetes Mellitus Tipe 2 - I Dewa Ayu Rismayanti; I Made Sundayana; Putu Agus Ariana; Mochamad Heri (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effect of diabetes education on blood glucose levels in type 2 DM patients. The research design used was pre-experimental with one group pre-post-test design. The results showed decreased blood glucose levels after intervention in diabetes education with a p-value = 0.000. The mean blood sugar level before the intervention was 244.19 and after the intervention was 166.06. In conclusion, diabetes education as diabetes management can affect type 2 DM patients' self-management, one of which is by monitoring blood sugar. Providing education can be influenced by several factors, such as patient factors, educators or education provider’s factors, and the length of the education supplied. Keywords: Type 2 Diabetes Mellitus, Education, Blood Glucose, Self Management